Pengaruh Motivasi Kerja dan Kompensasi terhadap Kepuasan Kerja Pegawai Kantor Pertanahan Kabupaten Buleleng - Komang Tri Sukma Pratiwi; Krisna Heryanda (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the effect of work motivation and compensation on job satisfaction among employees of the Land Office of Buleleng Regency. The study is motivated by the importance of job satisfaction as a key factor in supporting employee performance, loyalty, and productivity in delivering land administration services to the public. This research employs a causal quantitative design with the entire population of employees at the Land Office of Buleleng Regency as respondents. Data were collected through questionnaires that had undergone validity and reliability tests to ensure the appropriateness of the research instruments. The data were then analyzed using multiple linear regression with SPSS version 26 for Windows. The results show that work motivation has a positive and significant effect on employee job satisfaction at the Land Office of Buleleng Regency. Compensation also has a positive and significant effect on job satisfaction. In addition, work motivation and compensation simultaneously have a significant effect on job satisfaction. These findings indicate that good work motivation and fair, appropriate, and adequate compensation can improve employee job satisfaction. However, there are still other factors outside the research model that also influence job satisfaction and may be examined in future studies. Therefore, the management of motivation and compensation should be considered as an organizational strategy to create a more conducive, professional, productive, and sustainable work environment.